Greek Approach on the Israeli- Palestinian Conflict (1948-2015) - Μπίσδα - Ρωτίδη, Δέσποινα (Πανεπιστήμιο Πελοποννήσου, 2015)
This paper will examine the Greek approach kept on the Israeli- Palestinian conflict from 1948 until 2015. Considering that the conflict has historically evolved from a local scale to a large-scale regional one, the so-called Arab- Israeli conflict, Greek Middle Eastern policy has drawn upon the relevant developments. Providing that Greek policy has been driven by national interests maintained in the region, Greek governments adopted a certain attitude towards the conflict. Since the post- war period and up to the 1980s, Greek policy in the Middle East was mostly pro- Arab, whereby, Greek- Israeli relations remained cold and antagonistic. The main reasons behind this inverse relationship of Greece with the Arabs and the Jews were specific national interests preserved, such as to obtain Arab support in the Greek- Turkish dispute over Cyprus and to protect Greek communities in the Arab states. Therefore, Athens recognized only de facto the Jewish state in 1949. Although Greece supported for the recognition of Palestinian rights, including those of self-determination and statehood, it also supported for the right of Israel to exist in peace. The end of the 1980s brought a significant change in Greek Middle Eastern policy, particularly after Greek- Israeli normalization of relations in 1990. As the country pursued a policy of greater accommodation with Israel, bilateral relations improved substantially, particularly after the late 1990s. Since 2010, Greek- Israeli relations strengthened further, however not at the expense of its Arab allies. As a result, support for the creation of two states continued steadfastly, while this remains the current position of the present government on the Palestinian issue.
Η ελληνική προσέγγιση στην Ισραηλινό-Παλαιστινιακή Διένεξη (1948-2015)
Keywords: Αραβο-Ισραηλινή Σύγκρουση; Ελλάδα--Εξωτερικές σχέσεις--Ισραήλ; Ισραήλ--Σχέσεις--Παλαιστίνη; Μέση Ανατολή--Πολιτική και διακυβέρνηση; Ισραηλινό-παλαιστινιακή διαμάχη; Ελληνική μεσανατολική πολιτική; Ελληνοϊσραηλικές σχέσεις